Cerebello-Cortical Alterations Linked to Cognitive and Social Problems in Patients With Spastic Paraplegia Type 7: A Preliminary Study - Lupo, Michela; Olivito, Giusy; Clausi, Silvia; Siciliano, Libera; Riso, Vittorio; Bozzali, Marco; Santorelli, Filippo M.; Silvestri, Gabriella; Leggio, Maria (Frontiers in Neurology, 2020)
Spastic paraplegia type 7 (SPG7), which represents one of the most common forms of autosomal recessive spastic paraplegia (MIM#607259), often manifests with a complicated phenotype, characterized by progressive spastic ataxia with evidence of cerebellar atrophy on brain MRI. Recent studies have documented the presence of peculiar dentate nucleus hyperintensities on T2-weighted images and frontal executive dysfunction in neuropsychological tests in SPG7 patients. Therefore, we decided to assess whether any particular MRI pattern might be specifically associated with SPG7 mutations and possibly correlated with patients' cognitive profiles. For this purpose, we evaluated six SPG7 patients, studying the cerebello-cortical network by MRI voxel-based morphometry and functional connectivity techniques, compared to 30 healthy control subjects. In parallel, we investigated the cognitive and social functioning of the SPG7 patients. Our results document specific cognitive alterations in language, verbal memory, and executive function in addition to an impairment of social task and emotional functions. The MRI scans showed a diffuse symmetric reduction in the cerebellar gray matter of the right lobule V, right Crus I, and bilateral lobule VI, together with a cerebral gray matter reduction in the lingual gyrus, precuneus, thalamus, and superior frontal gyrus. The evidence of an over-connectivity pattern between both the right and left cerebellar dentate nuclei and specific cerebral regions (the lateral occipital cortex, precuneus, left supramarginal gyrus, and left superior parietal lobule) confirms the presence of cerebello-cortical dysregulation in different networks involved in cognition and social functioning in SPG7 patients.